Sensitive skin is highly frequent in extrinsic atopic dermatitis and correlates with disease severity markers but not necessarily with skin barrier impairment. Issue 1 (January 2018) - Yatagai, Tsuyoshi; Shimauchi, Takatoshi; Yamaguchi, Hayato; Sakabe, Jun-ichi; Aoshima, Masahiro; Ikeya, Shigeki; Tatsuno, Kazuki; Fujiyama, Toshiharu; Ito, Taisuke; Ojima, Toshiyuki; Tokura, Yoshiki
Highlights: The frequency of sensitive skin is higher in atopic dermatitis patients than in healthy subjects. The frequency of sensitive skin is higher in extrinsic atopic dermatitis patients than in intrinsic atopic dermatitis patients. Sensitive skin is associated with atopic dermatitis severity, but not necessarily with barrier condition. Abstract: Background: Sensitive skin is a condition of cutaneous hypersensitivity to environmental factors. Lactic acid stinging test (LAST) is commonly used to assess sensitive skin and composed of four distinct sensations (pain, burning sensation, itch, and crawly feeling). A link between sensitive skin and barrier dysfunction has been proposed in atopic dermatitis (AD) patients. However, clinical and laboratory factors that are associated with sensitive skin remain unelucidated. Objective: To investigate relationship between sensitive skin and AD-associated markers. Methods: Forty-two Japanese AD patients and 10 healthy subjects (HS) were enrolled. AD patients were divided into extrinsic (EAD; high IgE levels) and intrinsic (IAD; normal IgE levels) types. We conducted 1% LAST by assessing the four distinct sensations and calculated the frequencies of sensitive skin in EAD, IAD, and HS. We also performed clinical AD-related tests, including transepidermal water loss (TEWL), visual analogue scale (VAS) of pruritus, and quality of life, and measured laboratory markers, including blood levels of IgE, CCL17/TARC, lactate dehydrogenase (LDH) and eosinophil counts, and concentration levels of serum Th1/Th2 cytokines. Filaggrin ( FLG ) mutations were examined in 21 patients. These values were subjected to correlation analyses with each of the four sensation elements. Results: According to the standard criteria for LAST positivity, the frequencies of LAST-positive subjects were 54.8% and 10.0% in AD and HS, respectively ( P  = 0.014). EAD patients showed a significantly ( P  = 0.026) higher frequency of positive LAST (65.6%) than did IAD patients (20.0%). Among the four LAST sensation elements, the crawly feeling and pain scores positively correlated with VAS of pruritus, total serum IgE, mite-specific IgE, CCL17/TARC, and/or LDH. There was no association of the LAST scores with serum Th1/Th2 cytokine levels. Notably, neither TEWL nor FLG mutations correlated with LAST positivity or any sensation scores. Conclusions: The frequency of sensitive skin is higher in EAD than in IAD. Sensitive skin is associated with AD severity, but not necessarily with barrier condition.